1991
DOI: 10.1037/0033-295x.98.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic systems model of cognitive and language growth.

Abstract: In the first part of the article, a conceptual framework is sketched to define cognitive growth, including language growth, as a process of growth under limited resources. Important conceptsare the process, level, and rate of growth; minimal structural growth level; carrying capacity and unutilized capacity for growth; and feedback delay. Second, a mathematical model of cognitive growth under limited resources is presented, with the conclusion that the most plausible model is a mode] of logistic growth with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
282
0
10

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(296 citation statements)
references
References 72 publications
4
282
0
10
Order By: Relevance
“…In our view, research from this theoretical perspective has made substantial contributions to the field of motor development (Thelen & Ulrich, 1991) and language development (Van Geert, 1991, 1993 but has yet failed to make serious inroads into other aspects of developmental research and theorizing. Although one could argue that this stems from problems with researchers understanding the theory (Lewis, 2000), we suggest that the problem is deeper.…”
Section: Dynamic Systems Approachesmentioning
confidence: 99%
“…In our view, research from this theoretical perspective has made substantial contributions to the field of motor development (Thelen & Ulrich, 1991) and language development (Van Geert, 1991, 1993 but has yet failed to make serious inroads into other aspects of developmental research and theorizing. Although one could argue that this stems from problems with researchers understanding the theory (Lewis, 2000), we suggest that the problem is deeper.…”
Section: Dynamic Systems Approachesmentioning
confidence: 99%
“…Bever's (1982) research revealed regressive mechanisms in linguistic and cognitive development, due to internal restructuring of knowledge. Geert (1991), likewise, proposed regressive mechanisms in speech and general developmental process. Thelen and Smith (1994) accounted for the disappearance of reflex behaviors such as automatic walking, as "adaptive solutions to ontogenetic changes in life's demands."…”
mentioning
confidence: 99%
“…These reorganizations appear to be marked by discontinuities, that is, sudden spurts or changes in the behavior patterns. There has been much research on the qualitative changes occurring in the process of development, known in the literature as transitions (Connell & Furman, 1984;Elman et al, 1996;Fisher, Pipp, & Bullock, 1984;Fisher & Rose, 1994;Geert, 1991Geert, , 1997KarmiloffSmith, 1994;Johnson, 1997;Magnusson & Cairns, 1996;McCall, Eichnor, & Hogarthy, 1977;Reznick, Corley, & Robinson, 1997;Schore 1994;Thelen & Smith, 1994;Towen, 1998;Trevarthen, 1982aTrevarthen, , 1995.…”
mentioning
confidence: 99%
“…Although Muthén's GMM is capable of combining variable-centered and pattern-centered approaches to studying change (Muthén & Muthén, 2000), a major limitation is that it is built on a linear system of equations, where fixed and unique effects cannot both enter a change model nonlinear in its parameters. An increased appreciation of models of change nonlinear in their parameters is beginning to gain ground in the behavioral, educational, and social sciences (e.g., see Cudeck & Harring, 2007, for a recent review; see also Browne & du Toit, 1991;Burchinal & Appelbaum, 1991;Cudeck, 1996;van Geert, 1991). Models nonlinear in their parameters (e.g., negative exponential, logistic, Gompertz, etc.)…”
mentioning
confidence: 99%